1999
DOI: 10.3354/meps183115
|View full text |Cite
|
Sign up to set email alerts
|

A proline-rich peptide originating from decomposing mangrove leaves is one natural metamorphic cue of the tropical jellyfish Cassiopea xamachana

Abstract: A proline-rich peptide originating from decomposing mangrove leaves is one natural metamorphic cue of the tropical jellyfish Cassiopea xamachana 'Lehrstuhl fiir Spezielle Zoologie, Ruhr-Universitit. D-44780 Bochum. Germany 'Institute of Ecology, University of Georgia, Athens. Georgia 30602-2602. USA 3Complex Carbohydrate Research Center, University of Georgia, Athens. Georgia 30602-4712, USA ABSTRACT: Planula larvae of the scyphozoan Cassiopea xamachana settle and n~etamorphose on degrading mangrove leaves of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…As with previous studies (7, 21), C. xamachana settled and metamorphosed in response to natural substrates. We found larvae responded to both organic and inorganic substrates, including sand and bivalve shell fragments collected from onshore and offshore sites (Fig.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…As with previous studies (7, 21), C. xamachana settled and metamorphosed in response to natural substrates. We found larvae responded to both organic and inorganic substrates, including sand and bivalve shell fragments collected from onshore and offshore sites (Fig.…”
Section: Resultssupporting
confidence: 86%
“…Cholera toxin isolated from V. cholerae was also found to induce settlement and metamorphosis (19), and an extract from collagen digested by V. alginolyticus was also found to be inductive (20). In their natural environment, brooded C. xamachana larvae are released into the water column and will often settle preferentially onto the underside of degrading mangrove leaves (7, 21). When treated with antibiotics, larval settlement and metamorphosis is abolished in response to mangrove leaves.…”
Section: Introductionmentioning
confidence: 99%
“…35,37 In contrast, larval settlement of the tropical species C. xamachana is induced by a 5.8 kDa peptide rich in proline and glycine produced by bacterial decomposition of mangrove leaves of Rhizophora mangle, though it was effective only at a high concentration (86 µM). 39, 40 Larvae of the stony coral Agaricia humilis settle and metamorphose in response to a highly sulfated lipoglycosaminoglycan containing repeating β (1,4)-linked N-acetyllactosamine sulfate units with aliphatic side chains present on the surface of crustose coralline red algae such as Hydrolithon boergesenii. 41-43 A bacterial species of Pseudoalteromas isolated from the crustose coralline red alga H. onkodes induced larval metamorphosis in the coral Acropora willisae, 44 but no chemical characterization of the cue was made.…”
Section: Hydroids and Coralsmentioning
confidence: 99%
“…Cholera toxin isolated from V. cholerae was also found to induce settlement and metamorphosis ( 19 ), and an extract from collagen digested by V. alginolyticus was also found to be inductive ( 20 ). In their natural environment, brooded C. xamachana larvae are released into the water column and will often settle preferentially onto the underside of degrading mangrove leaves ( 7 , 21 ). When treated with antibiotics, larval settlement and metamorphosis is abolished in response to mangrove leaves.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest bacteria associated with degrading leaves may be a source of the inductive cue of Cassiopea . In a follow-up study, Fleck and Fitt ( 21 ) showed a water soluble, 5.8 kDa proline-rich peptide extracted from degraded mangrove leaves to be an inducer of settlement in C. xamachana . However, the originating bacterial source of the cue, and whether the cue is a by-product of leaf degradation, remains unknown.…”
Section: Introductionmentioning
confidence: 99%